A representation of cyclically compact operators on Kaplansky-Hilbert modules - GÖNÜLLÜ, UĞUR (Springer Basel Ag, Picassoplatz 4, Basel, 4052, Switzerland, 2016)
We give a representation of cyclically compact self-adjoint operators on Kaplansky-Hilbert modules and characterize the global eigenvalues of such operators by a sequence consisting of their global eigenvalues taken in the corresponding representation.
Keywords: Kaplansky-Hilbert module; Cyclically compact operator; Global eigenvalue; Diagonalizing Matrices